Analysis of Factors Related to Stigma of Health Worker and Medical Personnel Towards Hepatitis B at RSUDZA Banda Aceh - Azzaki Abu Bakar; Fauzi Yusuf; Teuku Renaldi; Liza Salawati; Pocut Diva Mahesa; Meutia Nailan Edward (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy)
Background: Hepatitis B is one of the infection disease that attacks liver and is often accompanied by stigma including among health worker and medical personnel. This research aiming for analyze related factors with the stigma of health worker and medical personnel towards Hepatitis B at RSUDZA Banda Aceh.